144 Access to permanent opioid disposal sites in the state of michigan. (19th September 2017) - Steiger, Rena; Khalsa, Caitlin; Schwartz, Alexander; Hurley, John; Baker, Michaella; Lee, Jay; Englesbe, Michael
Abstract : Statement of Purpose: The majority of opioids prescribed following procedural care remain unused, and are a common source of nonmedical opioid misuse and accidental poisonings. Due to the importance of removing unused opioids from the home, we sought to describe access to permanent opioid disposal sites in the state of Michigan. Methods/Approach: We identified and surveyed all sites currently authorised by the Drug Enforcement Administration (DEA) to collect opioids. The distance between the population-weighted centroid of each census block group in Michigan and the nearest opioid collection site was calculated using ArcGISÂ Network Analyst. These distances were then aggregated to the census tract level. Each census tract was categorised as urban or rural, low-income, or low-access (average distance to disposal site >1 mile for urban tracts and >10 miles for rural tracts). Results: We identified 819 DEA-authorised opioid disposal sites: 84% law enforcement agencies, 15%, pharmacies, and 1% other. Of these, 92% of sites responded, and 58% reported accepting opioids. The majority of individuals reside in areas with low-access (78%) to opioid disposal sites, including 94% of urban residents and 39% of rural residents. Overall, 31% reside in both low-income and low-access census tracts. The average distance to the nearest opioid disposal site was 4.0 miles, but ranged from 2.5 to 13.0 miles depending on census tract characteristic. Even after considering how access would change if all DEA-authorised sites collected opioids, distances changed minimally. Conclusions: In Michigan, opioid disposal sites are primarily law enforcement agencies, and only 58% of DEA-authorised sites report accepting opioids. Expanded DEA registration and authorisation to create safe and convenient opioid disposal options is paramount to curb the opioid crisis. Significance and Contributions to Injury and Violence Prevention Science: To our knowledge, our study is the first to quantify the state-wide accessibility of opioid disposal locations.